KERENTANAN EROSI DI DAERAH MANADO DAN SEKITARNYA, SULAWESI UTARA - S. Hidayat; Suharsono Suharsono (Pusat Survei Geologi, 2007)
Evolution cycle of landform in Manado and surrounding area is caused by weathering, erosion, transportation, sedimentation, and human factors. These processes have occurred since the land existence, and theywere strongly accelerated by human activities.Based on slope level, soil/rock type, vegetation/land covers, and erosion type, the erosion susceptibility in the studied area can be grouped into: high, medium, low, and no erosion.Very high erosion occurs on landform of volcanic cone a and b, volcanic slope a and b, mountain dissected volcanic slope and dissected straight volcanic mountain. High erosion occurs on landform of solfatara field, fumarola, volcanic foot slope b, volcanic mountain slope elongated dissected, volcanic slope c, residual hill and lava flow. Medium erosion occurs on landform of volcanic foot slope a and alluvium fan. Lowerosion occurs on landform of volcanic foot slope c, intermountain plane and flood plain. No erosion occurs on landform of alluvial.Keyword: erosion succeptibility, Manado, weathering, transportation, sedimentation